'We are data rich but information poor': how do patient-reported measures stimulate patient involvement in quality improvement interventions in Swedish hospital departments?. Issue 3 (5th August 2022) - Bergerum, Carolina; Petersson, Christina; Thor, Johan; Wolmesjö, Maria
Abstract : Objective: This study aimed to investigate if and how patient-reported measures from national and local monitoring stimulate patient involvement in hospital quality improvement (QI) interventions. We were also interested in the factors that influence the level and degree of patient involvement in the QI interventions. Methods: The study used a qualitative, descriptive design. Inspired by the Framework Method, we created a working analytical framework. Four hospital departments participated in the data collection. Collaborating with a QI leader from each department, we identified the monitoring systems for the patient-reported measures that were used to initiate or evaluate QI interventions. Thereafter, the level and degree of patient involvement and the factors that influenced this involvement were analysed for all QI interventions. Data were mapped in an Excel spreadsheet to analyse connections and differences. Results: Departments used patient-reported measures from both national and local monitoring systems to initiate or evaluate their QI interventions. Thirty-one QI interventions were identified and analysed. These interventions were mainly conducted at the direct care and organisational levels. By participating in questionnaires, patients were involved to the degree of consultation. Patients were not involved to the degree of partnership and shared leadership for the identified QI interventions. Conclusions: Overall, hospital departments have limited knowledge regarding patient-reported measures and how they are best applied in QI interventions and how they support improvements. Applying patient-reported measures to hospital QI interventions does not enhance patient involvement beyond the degree of consultation.